Pengaruh Pemberian Nilai Konsentrasi Tepung Spirulina platensis yang Berbeda Pada Pakan Terhadap Peningkatan Warna Ikan Komet (Carassius auratus) Effect of Spirulina platensis Concentration in Diet to Increase Color of Comet Fish (Carrassius auratus) - Wildan Panjaitan; Eri Yusni; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Comet fish (Carassius auratus) is a kind of ornamental fish and very popular in the world. Comet fish has a distinctive feature that can be seen from the beautiful color, beutiful fins especially elongated tail fin, and makes the comet fish has a high selling value. The color should be upgraded and maintained its quality. Such efforts to increase color has be done by adding natural pigment resources into the feeds. Natural pigment resources can be obtained from Spirulina platensis, the Spirulina were give 1 %, 3 %, and 5 % for 30 days. The purpose of this research is to determine dosage of Spirulina platensis make it optimal to increase the color of Comet fish. This Research using Complete Random Design (CRD) with three treatment repetition and control. The results of 3% Spirulina was significant bright color, compared of 1% and 5% Spirulina were give. But for the growth and length of Comet fish has no significant diffrence.Keywords : Carassius auratus, Comet fish, Spirulina platensis, colour